High resolution imaging for inspection of laser beam melting systems - zur Jacobsmuhlen, Joschka; Kleszczynski, Stefan; Schneider, Dorian; Witt, Gerd (2013 IEEE International Instrumentation and Measurement Technology Conference (I2MTC), 2013)
Laser Beam Melting (LBM) allows the fabrication of three-dimensional parts from metallic powder with almost unlimited geometrical complexity and very good mechanical properties. LBM works iteratively: a thin powder layer is deposited onto the build platform which is then melted by a laser according to the desired part geometry. Today, the potential of LBM in application areas such as aerospace or medicine has not yet been exploited due to the lack of process stability and quality management. For that reason, we present a high resolution imaging system for inspection of LBM systems which can be easily integrated into existing machines. A container file stores calibration images and all layer images of one build process (powder and melt result) with corresponding metadata (acquisition and process parameters) for documentation and further analysis. We evaluate the resolving power of our imaging system and show that it is able to inspect the process result on a microscopic scale. Sample images of a part built with varied process parameters are provided, which show that our system can detect topological flaws and is able to inspect the surface quality of built layers. The results can be used for flaw detection and parameter optimization, for example in material qualification.